IDENTIFICATION OF GEOSTATIONARY SATELLITES BY THEIR PHOTOMETRIC AND DYNAMIC FEATURES, SOME PROBLEMS - Sukhov, P. P.; Sukhov, K. P. (Одеські астрономічні публікації, 2016)
It is possible to identify certain characteristics of geostationary satellites by studying their photometry. This paper reviews some of the technical problems and methodologies concerning photometry of satellites, as well as their identification by photometric characteristics. The existing methods of identifying geostationary satellites using photometry are also summarized. The present Database of photometric and dynamic characteristics of the GSS, additional information, simplifying the input of the inverse problem  all this allows modern methods to identify unknown GSS with a probability up to 80%.